(untitled) (BioLaw Journal - Rivista di BioDiritto, 2019)
DNA analysis as a tool for investigations and definitive proof offers great opportunities for crimes’ resolution, but it also has several downsides, such as the possible infringement of individual rights, ranging from privacy to habeas corpus. Both legislators and judges are called to face new challenges, as the recent Italian experience, with the creation of the national DNA database (which fully came into operation in 2017) has taught us; in the past, such challenges saw the Constitutional Court as the legitimacy guarantor of laws pertaining forced sampling, able to oversee that personal freedom would remain intact.